Perbaikan Kemasan Keju Gouda Muda Dengan menggunakan Quality Function Deployment (QFD) - Suroyo, Suroyo; , Siti Nandiroh, ST, M.Eng; , Indah Pratiwi, ST., MT (2016)
Marketing the spearhead from company to achieve succes. Whith the marketing, the company will continue to innovate that their products to be acceptable to consumers with price as expected consumers but still give a good quality. Cheese gouda is chees hard with the moisture ontent of 35-40%, from making cheese gouda from the netherland. Gouda itself is the name of the city is in the zoid holland, the netherlands. But Boyolalinow have the cheese producing cheese gouda whith standar making in accordance with the manufacturing the netherlands. Cheese gouda Boyolali still in the market share adjustment to compete with the competitor. Hence the researchers aims to understand atribut-atribut that influences the level paking cheese gouda young and cheddar cheese. Improved paking cheese gouda with the quality function deployment (qfd) the data drawn from consumer advocacy by filling the questionnaire open and later was continued to the questionnaire closed. data processing continued into the houde of quality(hoq). the result of this research suggests atribut-atribut affecting consumer advocacy in determining the purchase price, packaging, security food, the cheese, nutrition, writing letters, endurance packaging.